A Combined Electromagnetic Levitation Melting, Counter‐Gravity Casting, and Mold Preheating Furnace for Producing TiAl Alloy. Issue 2 (25th September 2017) - Yang, Jieren; Wang, Hu; Wu, Yulun; Wang, Xuyang; Hu, Rui
Abstract : In this work, the authors describe the development of TiAl castings over a wide range of approaches. To overcome casting defects and cracks that appear in TiAl castings, a novel furnace is designed and constructed. The design combines induction skull melting, counter‐gravity casting, and mold heating, which facilitates both filling and microstructure formation via a controllable process. This aim is to improve shaping capabilities and microstructural control for TiAl castings. Melting and casting experiments on TiAl alloys with a nominal composition corresponding to Ti–48Al–2Cr–2Nb (at%) are carried out and discussed. X‐ray examinations indicate that the shaping of the TiAl components dose not contain macro casting defects, validating the advantages of this technique. The results are of interest to researchers devoted to technical innovations and modifications for TiAl casting at the industrial scale. Abstract : The design combines induction skull melting, counter‐gravity casting and mold heating a), which facilitates the shaping of the TiAl components b and c), and the decreasing of the defect d) via a controllable process. The results are of interest to researchers devoted to produce high‐quality TiAl castings.